Sequential Genome Editing and Induced Excision of the Transgene in N. tabacum BY2 Cells - Sheva, Maor; Hanania, Uri; Ariel, Tami; Turbovski, Albina; Rathod, Vishal Kumar Rameshchandra; Oz, Dina; Tekoah, Yoram; Shaaltiel, Yoseph (Frontiers in Plant Science, 2020)
While plant cells in suspension are becoming a popular platform for expressing biotherapeutic proteins, the need to pre-engineer these cells to better comply with their role as host cell lines is emerging. Heterologous DNA and selectable markers are used for transformation and genome editing designated to produce improved host cell lines for overexpression of recombinant proteins. The removal of these heterologous DNA and selectable markers, no longer needed, can be beneficial since they limit additional gene stacking in subsequent transformations and may pose excessive metabolic burden on the cell machinery. In this study we developed an innovative stepwise methodology in which the CRISPR-Cas9 is used sequentially to target genome editing, followed by its own excision. The first step included a stable insertion of a CRISPR-Cas9 cassette, targeted to knockout the β(1,2)-xylosyltranferase (XylT) and the α(1,3)-fucosyltransferase (FucT) genes in Nicotiana tabacum L. cv Bright Yellow 2 (BY2) cell suspension. The second step included the excision of the inserted cassette of 14.3 kb by induction of specific gRNA designed to target the T-DNA boundaries. The genome editing step and the transgene removal step are achieved in one transformation run. This mechanism enables CRISPR genome editing and subsequently eliminating the introduced transgenes thus freeing the cells from foreign DNA no longer needed.